English proficiency tests in Indonesian university admission: A critical review of equity and culture - Azmy, Khairul; Akmaliyah, Nur; Asma, Asma (Lembaga Penelitian, Penerbitan, Pengabdian dan Pengembangan Masyarakat (LP4M) Unmuha, 2025)
This study critically examined the use of English-language proficiency tests, such as the TOEFL and IELTS, as gatekeeping tools for university admissions in Indonesia. While these tests serve as standardised indicators of academic readiness, their widespread application raises concerns about fairness, accessibility, and sociocultural implications, especially for students in rural areas. Grounded in sociocultural theories of language, identity, and power, and informed by contemporary research on language assessment and educational equity, this qualitative inquiry used critical autoethnography, reflective narratives, and critical analysis to explore two main focuses of the issue: why English proficiency tests are used as entrance requirements in a country where English is not the medium of daily communication, and how these tests affect students’ identities and opportunities. Findings showed that these tests often function beyond linguistic evaluation—symbolising institutional prestige, perpetuating social inequalities, and constructing identity hierarchies among students. The investigation is further enriched by contemporary research on language assessment and educational equity, which provides a framework for understanding how these tests may inadvertently perpetuate social inequalities and limit opportunities for certain student groups. The paper concludes by recommending inclusive language policies and enhanced access to language learning in rural Indonesia.